Determination of Heavy Metal Concentrations in Sediment of Bonny River, Nigeria - A. Bubu; C. P. Ononugbo; G. O. Avwiri (Archives of Current Research International, 2018)
Contamination of sediment by heavy metals is one of the global issues mostly in developing nations like Nigeria. Five heavy metal such Lead (Pb), Copper (Cu), Manganese (Mn), Zinc (Zn) and iron (Fe) in sediments from Bonny River in Rivers State were investigated. The increasing trend of metals was observed in sediments Cu ˂ Pb ˂ Zn ˂ Fe ˂ Mn. The mean concentration of the metals were 1.31, 3.95, 9.11, 15.07 and 31.54 mg/kg for Cu, Pb, Zn, Fe and Mn respectively. The concentration levels of all the heavy metals in sediment studied were lower than the safe values. The contamination factor calculated confirmed that the studied sediment were not polluted by these heavy metals. The Pollution load index (PLI) values were lower than one (˂ 1) in all the samples indicating good sediment quality. Geo-accumulation Index (Igeo) calculated was less than 0, likewise the enrichment factor values were less than 2 which implies deficiency to minimal enrichment. From the results obtained, the Bonny River sediments have low contamination level and are said to be unpolluted by all heavy metals. Therefore sediment from Bonny River is safe and can be used as a building material.